The Kentish-Frisian legal vocabulary - Daniela Fruscione (Filologia Germanica)
This essay deals with Anglo-Frisian “discourse” from both a historical and a philological point of view. It investigates the Kentish Frisian connection in the field of legal vocabulary. The precise relationship between Old English and Frisian is difficult to reconstruct because historical data about Frisia are scarce and contradictory, and because there is a lack of Frisian language material that is contemporary with Old English. Without intending to make a revolutionary new proposal, this essay highlights a few relevant semantic and morphological parallels between the catalogue of body injuries found in Æthelberht’s first English law and the much later Frisian legal documents. These parallels suggest an early contact between the two languages.